The Adjustment of International Institutions to Global Power Shifts: A Framework for Analysis. (17th November 2020) - Kruck, Andreas; Zangl, Bernhard
Abstract: As powers such as China and India rise, and powers such as the US or the UK decline, international institutions such as the United Nations Security Council, the World Trade Organization and the International Monetary Fund come under pressure to adapt to new power realities. In the wake of global power shifts, both emerging and established powers may challenge the institutional status quo. Contrary to what most power transition and power shift theories assume, challengers do not always draw on power bargaining to pursue institutional adjustment. In some issue areas, they do, but in others they employ alternative strategies including strategic cooptation, rhetorical coercion and principled persuasion. In order to contribute to a better understanding of institutional adjustments to global power shifts, the introduction to this special issue theorizes these various strategies. First, we conceptualize power bargaining, strategic cooptation, rhetorical coercion and principled persuasion as distinct strategies for institutional adjustment. Second, we elaborate on the conditions under which challengers choose particular strategies. Third, we specify the conditions under which challengers are able to achieve institutional adaptation through a particular strategy. Finally, we discuss broader implications for the future of the international order and the management of global power shifts.